Infective endocarditis presenting with loin pain. (11th January 2011) - Kohansal, Ali; Luyckx, Valerie A
Abstract : A 28-year-old previously healthy man presented to a peripheral hospital several hours after onset of acute right flank pain. A kidney stone was suspected clinically as the patient was otherwise well appearing, afebrile and normotensive. Renal function was normal and urinalysis showed no haematuria or white blood cells. A contrast CT scan of the abdomen revealed a filling defect in the ventral branch of the right renal artery with no distal perfusion suggesting a renal embolus. Subsequent investigations revealed blood cultures positive for coagulase negative staphylococcus and echocardiogram showed a bicuspid aortic valve, a dilated aortic root and moderately dilated ascending aorta. The patient was transferred to a tertiary care hospital and transesophageal echocardiogram revealed severe aortic insufficiency and thickening of the aortic valve suggestive of endocarditis. Following antibiotic treatment, blood cultures became negative and the patient underwent successful semi-urgent aortic root replacement. Renal function remained normal throughout.